2010
DOI: 10.1111/j.1365-2036.2010.04495.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized incidence and case fatality for upper gastrointestinal bleeding from 1999 to 2007: a record linkage study

Abstract: SUMMARY BackgroundUpper gastrointestinal (GI) bleeding is the most common emergency managed by gastroenterologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
145
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 29 publications
12
145
2
3
Order By: Relevance
“…A small study of less than 2000 patients from the north west of Scotland demonstrated a 2 fold difference in the occurrence of upper gastrointestinal haemorrhage between the least and most deprived, while a recent report from Wales also indicated that those from most deprived areas have the highest rate of hospitalization for upper gastrointestinal haemorrhage. 22,25 However both these studies found higher hospitalisation rates than previous studies and this raises questions of how their popu-CHAPTER 2: BACKGROUND: Occurrence and trends lations and cases were defined. Furthermore both studies only reported crude combined variceal and non variceal haemorrhage estimates and their methodology and limited size mean they did not investigate whether differences in age, gender, year or region might be responsible for the socioeconomic gradient.…”
Section: Chapter 2: Background: Occurrence and Trendsmentioning
confidence: 93%
See 3 more Smart Citations
“…A small study of less than 2000 patients from the north west of Scotland demonstrated a 2 fold difference in the occurrence of upper gastrointestinal haemorrhage between the least and most deprived, while a recent report from Wales also indicated that those from most deprived areas have the highest rate of hospitalization for upper gastrointestinal haemorrhage. 22,25 However both these studies found higher hospitalisation rates than previous studies and this raises questions of how their popu-CHAPTER 2: BACKGROUND: Occurrence and trends lations and cases were defined. Furthermore both studies only reported crude combined variceal and non variceal haemorrhage estimates and their methodology and limited size mean they did not investigate whether differences in age, gender, year or region might be responsible for the socioeconomic gradient.…”
Section: Chapter 2: Background: Occurrence and Trendsmentioning
confidence: 93%
“…35 Regional incidence within one country can also vary widely. The incidence in north west Scotland has been estimated to be 172/100,000, 22 the incidence in Wales has been estimated to be 134/100,000, 25 and the incidence in middle England has been estimated to be between 43/100,000 around Oxford 36 to 103/100,000 around the Thames and the Midlands. 23 The reason for these large regional differences within the UK is often thought to be deprivation.…”
Section: Chapter 2: Background: Occurrence and Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nonvariceal Upper Gastrointestinal Bleeding (NVUGIB) is a frequent cause for hospitalization (4,6,8,11,14,17,20) . Recent clinical studies demonstrate that the outcome of these patients can be improved when clinical resources are improved, decreasing the recurrence of bleeding (2,13,15,19) , the need for transfusion (13,19) and surgery (13) and reducing the length of stay and hospital costs (13,19) .…”
Section: Introductionmentioning
confidence: 99%